2000
DOI: 10.1111/j.1749-7345.2000.tb00892.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Selected Parameters for Growth of Larval and Juvenile Black Sea Bass Centropristis striata L.

Abstract: Abstract.— The black sea bass Centropristis striata L. endemic to the U. S. Atlantic and Gulf of Mexico coasts is a highly sought species that commands a high price in the marketplace. Investigations were undertaken to determine the basic requirements for culture of sea bass larvae and juveniles. Adult black sea bass were captured from the wild and were found to be robust and to adapt well to captivity. Larvae were obtained by strip spawning of these adults and survived and grew at higher rates in seawater sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 18 publications
0
36
0
Order By: Relevance
“…Walker and Moroney (2000) found that adult black sea bass fed a salmon diet (45% protein and 26% lipid) grew significantly larger than fish fed a trout diet (38% protein and 8% lipid). Similarly, Berlinsky et al (2000) found that subadult black sea bass fed a diet containing 52% protein and 18% lipid were significantly larger than fish fed a diet containing 38% protein and 12% lipid. Copeland et al (2002) also reported higher growth rates in subadult black sea bass fed commercial diets containing between 50 and 56% proteins when compared with diets containing 41–45% protein.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Walker and Moroney (2000) found that adult black sea bass fed a salmon diet (45% protein and 26% lipid) grew significantly larger than fish fed a trout diet (38% protein and 8% lipid). Similarly, Berlinsky et al (2000) found that subadult black sea bass fed a diet containing 52% protein and 18% lipid were significantly larger than fish fed a diet containing 38% protein and 12% lipid. Copeland et al (2002) also reported higher growth rates in subadult black sea bass fed commercial diets containing between 50 and 56% proteins when compared with diets containing 41–45% protein.…”
Section: Discussionmentioning
confidence: 83%
“…Investigations into commercial production of the black sea bass were initiated in response to the need for diversification of the marine finfish aquaculture industry in the Northeastern USA. Like many other species in the family Serranidae, black sea bass have great potential for mariculture as they are hardy, have high market value, and have limited seasonal supply (Tucker 1984; Kim 1987; Costa and Provenzano 1993; Berlinsky et al 2000; Walker and Moroney 2000). In response to this, several studies have focused on captive spawning (Watanabe et al 2003), larviculture (Berlinsky et al 2000), grow‐out of juveniles and subadult captive wild black sea bass (Copeland et al 2002; Cotton et al 2003), and economic evaluation of ongrowing of captive wild black sea bass (Copeland et al 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently considered overexploited, annual US commercial landings of black sea bass have decreased from approximately 4.3 million kg in 1963 to approximately 1.7 million kg in 2003, which has resulted in premium ex‐vessel prices for whole fish ranging from $US3 to 8/kg 2 Due to their high value and limited supply, efforts to develop culture methods for black sea bass have intensified in recent years. While research has been and continues to be conducted on topics including reproduction, 3–5 larviculture, 3,6 , 7 nutrition 8–10 and ongrowing procedures, 9–13 relatively little information exists with respect to the environmental requirements of black sea bass and their tolerance to culture conditions and variables…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about the nutrient requirements of black sea bass. Previous investigations with black sea bass have focused on growth and performance of fish fed commercial feeds formulated for other species 4–10 …”
Section: Introductionmentioning
confidence: 99%